Regularities of visible photoluminescence creation in low-dimensional silicon structures - Manoilov, E.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The evolution of time-resolved photoluminescence (PL) spectra in Au-doped nanocrystalline silicon films produced by laser ablation has been studied. The PL spectra with a relaxation time of nanoseconds are broad; they lie in the energy range 1.4-3.2 eV with a peak at 2.4-2.8 eV. At the longest times of tens of microseconds, the spectra become narrower, with a peak at 1.6 eV. At intermediate times, two bands are observed: low-energy (1.6 eV) and high-energy, with the peak shifting from 2.7 to 2.1 eV with time increasing. The data are discussed in terms of quantum confinement, dielectric amplification, and manifestation of kinetically coupled electron-hole and exciton subsystems. Ions and atoms of gold passivate dangling bonds at Si surface and serve as catalysts for oxidation of nanocrystals.